2021
DOI: 10.1002/alz.12512
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of subjective cognitive decline associated with amyloid positivity

Abstract: Introduction:The evidence for characteristics of persons with subjective cognitive decline (SCD) associated with amyloid positivity is limited. Methods: In 1640 persons with SCD from 20 Amyloid Biomarker Study cohort, we investigated the associations of SCD-specific characteristics (informant confirmation, domain-specific complaints, concerns, feelings of worse performance) demographics, setting, apolipoprotein E gene (APOE) ε4 carriership, and neuropsychiatric symptoms with amyloid positivity. Results: Betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 38 publications
5
29
1
Order By: Relevance
“…Our finding concerning the association between SMC and brain amyloid index is consistent with the results of several studies on SMC–Aβ association using amyloid PET imaging or plasma Aβ measurements in non-demented individuals ( Amariglio et al, 2012 ; Perrotin et al, 2012 ; Kryscio et al, 2014 ; Cantero et al, 2016 ; Kim et al, 2019 ; Hong et al, 2021 ; Janssen et al, 2021 ; Tort-Merino et al, 2021 ). Although some studies using amyloid PET imaging did not identify a significant SMC–Aβ association ( Chetelat et al, 2010 ; Rodda et al, 2010 ), these reported a trend toward an SMC–Aβ association ( Chetelat et al, 2010 ; Rodda et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding concerning the association between SMC and brain amyloid index is consistent with the results of several studies on SMC–Aβ association using amyloid PET imaging or plasma Aβ measurements in non-demented individuals ( Amariglio et al, 2012 ; Perrotin et al, 2012 ; Kryscio et al, 2014 ; Cantero et al, 2016 ; Kim et al, 2019 ; Hong et al, 2021 ; Janssen et al, 2021 ; Tort-Merino et al, 2021 ). Although some studies using amyloid PET imaging did not identify a significant SMC–Aβ association ( Chetelat et al, 2010 ; Rodda et al, 2010 ), these reported a trend toward an SMC–Aβ association ( Chetelat et al, 2010 ; Rodda et al, 2010 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although some studies using amyloid PET imaging did not identify a significant SMC-Aβ association (Chetelat et al, 2010;Rodda et al, 2010), these reported a trend toward an SMC-Aβ association (Chetelat et al, 2010;Rodda et al, 2010). These findings suggests that SMC is a risk factor for AD or related cognitive impairment (Commissaris et al, 1994(Commissaris et al, , 1998Winblad et al, 2004;Reid and Maclullich, 2006;Reisberg et al, 2008;Jessen et al, 2010Jessen et al, , 2014aChoe et al, 2018;Janssen et al, 2021;Tort-Merino et al, 2021) because Aβ pathology is the earliest key pathology of AD (Braak and Braak, 1991;Tobiansky et al, 1995;Jack et al, 2010). In addition, Aβ may show a mediation effect on the association between SMC and AD or related cognitive impairment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SCD is not specific to AD and can also be caused by normal aging, depression, and other psychiatric and neurologic disorders [5]. In addition, a recent meta-analysis reported substantial variation of the proportion of SCD cases with amyloid pathology among individual samples, depending on the specific recruitment criteria and settings [6]. In those SCD cases, who progress to dementia, DAT is the most common, but other dementia types also occur [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the stable amyloid-negative group, depressive symptoms may be associated with increased awareness of cognitive failures, consequently leading to seek medical consultation. Studies on subjective cognitive impairment (SCI) have shown that patients with a history of medical help-seeking behaviour had lower amyloid and higher depressive symptoms [28], and that feelings of worse cognitive performance were not predicted by amyloid positivity in younger individuals [29]. Although patients undergoing amyloid PET in our Clinic do have some degree of objective impairment by definition [16], a similar mechanism to that seen in SCI may apply to the stable amyloid-negative group.…”
Section: Discussionmentioning
confidence: 64%